ANALISIS KEMAMPUAN MENULIS PANTUN PADA SISWA KELAS VB SD XAVERIUS 4 PALEMBANG - Mahalda Sitorus (Universitas Katolik Musi Charitas, 2020)
This research study aims to describe the ability of students in writing rhymes for class VB SD Xaverius 4 Palembang. In education in Indonesia, Indonesian is an important subject. In Indonesian lessons, there is rhyme material. In this modern era, rhymes are rarely used in special occasions such as weddings, thanksgiving events and traditional events. This stems from the negative impact of globalization which makes people adopt unpopular lifestyles such as western culture. Whereas pantun is one of the nation's cultures that must be studied. Therefore, I was interested in researching the students' rhyme writing skills. This research is a qualitative research. The population in this study amounted to 91. The sample in this study amounted to 25. The data collection technique was done by means of interviews, tests, and documentation. Validation is done by validating the triangulation of researchers. From the results of the research that has been done, it can be concluded that students are very capable in writing rhymes. This can be proven by the average value obtained is 91.1 and it is in the very good category. Although the research results show that students are very capable in writing rhymes, they are still students who do not meet several requirements in writing rhymes.